THE PHENOMENON OF FEMICIDE IN BRAZIL AND THE LEGAL PROVISION FOR PROTECTION AGAINST VIOLENCE AGAINST WOMEN - e Silva, Francisca de Sousa; Lima, Maísa Rocha; do Rego, Elson José; Sampaio, Vanessa Nunes de Barros Mendes; do Nascimento, Justina Alzira Soares; Santos, Jane Karla de Oliveira; Ferreira, Luiza Lourdes Pinheiro Leal Nunes (Seven Editora, 2025)
This article analyzes femicide in Brazil in the light of criminal legislation and international treaties for the protection of women. From the enactment of Law No. 13,104/2015 and Law No. 14,994/2024, we seek to understand the normative advances and the practical obstacles in their implementation. The research is qualitative, bibliographic and documentary, based on contemporary doctrine, jurisprudence and official bibliographic data. The socio-cultural and institutional impacts and the need for conventionality control to ensure the effectiveness of women’s rights are also discussed. The study includes analysis of jurisprudence, case study and methodological framework. The objective is to offer a critical and purposeful overview of the criminal protection of women in Brazil against femicide. DOI: https://doi.org/10.56238/sevened2025.018-044